Attachment to the Amazon rainforest: constitutive aspects and their predictors - Rosa, Daniele da Costa Cunha Borges; Higuchi, Maria Inês Gasparetto; Roazzi, Antonio (Paidéia (Ribeirão Preto), 2021)
This investigation aims to contribute to the understanding of the attachment to the Amazon rainforest and its predictors, considering the dimensions that characterize this extensive environment. Five instruments were administered to 333 individuals of both genders, over the age of 18, from the cities of Ceres and Manaus, evaluating the Ecological Affinity profile; Attachment to the Amazon rainforest; Experiences in Nature; Knowledge of the Amazon rainforest; and Socioeconomic factors. The results confirm that attachment depends on the length of stay in the place. Data shows that the ecological affinity profile plays an important role in the attachment to a natural environment, suggesting that this relationship is strengthened by understanding the characteristics of this environment and its experiences. Based on the perspective of Environmental Psychology, this study advances knowledge on place attachment predictors and provides important arguments for the development of pro-environmental interventions focused on emotional and experiential aspects.